2014
DOI: 10.5897/ajbr2014.0768
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary tyrosine on serum cholesterol fractions in rats

Abstract: The present study was undertaken to measure the effects of dietary tyrosine added to rat diet on serum cholesterol levels in the rat. A total of twenty Wistar strain albino rats were fed with different doses of tyrosine enriched diets containing 0.8 g/100 g, 1.0 g/100 g and 1.2 g/100 g. After 3 weeks of experimental feeding, there was significant increase (p<0.05) in total postprandial serum cholesterol of rats fed with graded of tyrosine when compared with the normal control. Same trend was followed in the we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 25 publications
0
1
0
Order By: Relevance
“…It is generally acknowledged that women are more likely than men to have UTIs due to their reproductive function [26][27][28][29][30]. This is supported by another study in Ethiopia, which showed that female patients with diabetes were 3.77 times more likely to develop UTI than their counterparts [30][31][32][33][34]. This also appears to be connected to proximity to the anus, physiological bladder alterations brought on by aging or shortness of breath, and bladder neurological dysfunction [27][28][29][30][31][32]).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…It is generally acknowledged that women are more likely than men to have UTIs due to their reproductive function [26][27][28][29][30]. This is supported by another study in Ethiopia, which showed that female patients with diabetes were 3.77 times more likely to develop UTI than their counterparts [30][31][32][33][34]. This also appears to be connected to proximity to the anus, physiological bladder alterations brought on by aging or shortness of breath, and bladder neurological dysfunction [27][28][29][30][31][32]).…”
Section: Discussionmentioning
confidence: 92%
“…This could be due to the long-term effects of diabetes, such as neuropathy and an impaired immune system. Chronic hyperglycemia may cause renal papillary necrosis, nephropathy, and cystopathy, which increase the risk of UTI [29][30][31][32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…Studies in sub-Saharan African populations suggest that natural selection has acted on several genomic regions associated with obesity and type 2 diabetes, and a study that mapped the genetic risk of type 2 diabetes by measuring the allelic frequency of 16 diabetesassociated variants in 51 populations suggested that Africans face the greatest known genetic risk for type 2 diabetes of any ethnicity studied thus far [29][30][31][32][33][34][35][36][37]. Globally, 83.3% of diabetic patients have type 2 diabetes mellitus while almost 98% of diabetic patients below 15years have type 1 diabetes mellitus [38][39][40][41][42][43][44][45]. In a study conducted by Kajobba Dickson in Southwestern Uganda in 2016, it was revealed that about 79% of diabetic patients had type 2 DM and about 77% of them were 31-69 years indicating a strong association between diabetes and age [29-37].…”
Section: Discussionmentioning
confidence: 99%
“…These findings are in agreement with the report that was released by Ugandan ministry of health in 2014 that indicated that the onset of type 2 DM was in late 30s and the prevalence increased with age unlike type 1 DM that was dominate among those aged 15years ad below [33]. According to a study done by Kajoba Dickson, females were the most affected group (60%) for both type 2 and type 1 diabetes [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45]. Further analysis showed that diabetes type 2 was strongly affected by gender (p=0.035).…”
Section: Discussionmentioning
confidence: 99%
“…The lipid profile result (Table 3) showed a moderate attenuating effect on the serum total cholesterol, LDL, VLDL levels, and subsequently a significant increase in serum HDL in the male albino rats. The potential effects of the extract on the lipid profile may be associated with the decline in the synthesis of cholesterol and its metabolism, as well as the expression of signal receptors of LDL [37]. LDL plays a major role in the development of atherosclerosis, especially after their oxidation while HDL reverses cholesterol transport and transfer of cholesterol esters from cell membranes which free cholesterol to the core of the HDL and inhibits the oxidation of LDL [2,21].…”
Section: Discussionmentioning
confidence: 99%